Thioredoxin Modulates Cell Surface Hydrophobicity in Acinetobacter baumannii - May, Holly C.; Yu, Jieh-Juen; Shrihari, Swathi; Seshu, Janakiram; Klose, Karl E.; Cap, Andrew P.; Chambers, James P.; Guentzel, M. Neal; Arulanandam, Bernard P. (Frontiers in Microbiology, 2019)
Acinetobacter baumannii, a Gram-negative coccobacillus, has become a prevalent nosocomial health threat affecting the majority of hospitals both in the U.S. and around the globe. Microbial cell surface hydrophobicity (CSH) has previously been correlated with virulence, uptake by immune cells, and attachment to epithelial cells. A mutant strain of A. baumannii (ΔtrxA) lacking the redox protein thioredoxin A was found to be more hydrophobic than its wild type (WT) and complemented counterparts, as measured by both Microbial Adhesion to Hydrocarbon (MATH) and salt aggregation. The hydrophobicity of the mutant could be abrogated through treatment with sodium cyanoborohydride (SCBH). This modulation correlated with reduction of disulfide bonds, as SCBH was able to reduce 5,5'-dithio-bis-[2-nitrobenzoic acid] and treatment with the known disulfide reducer, β-mercaptoethanol, also decreased ΔtrxA CSH. Additionally, the ΔtrxA mutant was more readily taken up than WT by J774 macrophages and this differential uptake could be abrogated though SCBH treatment. When partitioned into aqueous and hydrophobic phases, ΔtrxA recovered from the hydrophobic partition was phagocytosed more readily than from the aqueous phase further supporting the contribution of CSH to A. baumannii uptake by phagocytes. A second Gram-negative bacterium, Francisella novicida, also showed the association of TrxA deficiency (FnΔtrxA) with increased hydrophobicity and uptake by J774 cells. We previously have demonstrated that modification of the type IV pilus system (T4P) was associated with the A. baumannii ΔtrxA phenotype and the Francisella FnΔtrxA mutant also was found to have a marked T4P deficiency. Interestingly, a F. novicida mutant lacking pilT also showed increased hydrophobicity over FnWT. Collective evidence presented in this study suggests that Gram-negative bacterial thioredoxin mediates CSH through multiple mechanisms including disulfide-bond reduction and T4P modulation.